Performance of grain maize (Zea mays) hybrids for dual utility in ideal maize agronomic conditions - RAJENDRAN, AMBIKA; SINGH, NIRUPMA; SINGODE, AVINASH (The Indian Journal of Agricultural Sciences, 2018)
Owing to rising demand, value addition, increased income, superior taste and texture, baby corn is gaining attention as a profitable crop. Superior maize (Zea mays L.) cultivars, good for grain yield, can also be exploited for baby corn, fodder, green cob etc. In this work, interest has been taken to evaluate 23 best experimental early single cross hybrids with regard to their baby corn suitability under ideal agronomic conditions of grain maize production. Denser planting and detasseling are the specific operations carried out to identify best hybrid for baby corn along with noting prolificacy and important baby corn quantity and quality based traits. CMLX325 and CMLX338 were found most useful for baby corn purpose. Such superior genotypes can act as genetic resource for baby corn improvement.